Ph(+)/VE-cadherin(+) identifies a stem cell–like population of acute lymphoblastic leukemia sustained by bone marrow niche cells - Wang, Lin (American Society of Hematology, 2007)
Although leukemic stem cells (LSCs) show a symbiotic relationship with bone marrow microenvironmental niches, the mechanism by which the marrow microenvironment contributes to self-renewal and proliferation of LSCs remains elusive. In the present study, we identified a unique subpopulation of Philadelphia chromosome–positive (Ph(+)) acute lymphoblastic leukemia (ALL) cells coexpressing markers of endothelial cells (including VE-cadherin, PECAM-1, and Flk-1) and committed B-lineage progenitors. After long-term coculture with bone marrow stromal cells, tumor cells formed hematopoietic colonies and cords, expressed early stem- cell markers, and showed endothelial sprouting. Gene expression profiles of LSCs were altered in the presence of stromal cell contact. Stromal cell contact promoted leukemic cell VE-cadherin expression, stabilized β-catenin, and up-regulated Bcr-abl fusion gene expression. Our study indicates that these specific tumor cells are uniquely positioned to respond to microenvironment-derived self-renewing and proliferative cues. Ph(+)/VE-cadherin(+) tumor subpopulation circumvents the requirement of exogenous Wnt signaling for self-renewal through stromal cell support of leukemic cell VE-cadherin expression and up-regulated Bcr-abl tyrosine kinase activity. These data suggest that strategies targeting signals in the marrow microenvironment that amplify the Bcr-abl/VE-cadherin/β-catenin axis may have utility in sensitizing drug-resistant leukemic stem cells.